Influence of hysteresis on the transient hygrothermal response of a hemp concrete wall. Issue 3 (4th May 2017) - Aït Oumeziane, Yacine; Moissette, Sophie; Bart, Marjorie; Collet, Florence; Pretot, Sylvie; Lanos, Christophe
Abstract : Building envelopes with bio-materials like hemp concrete are currently undergoing an increasing development due to their low environmental impact and their interesting hygrothermal properties. This kind of hygroscopic material is characterized by a hysteretic behaviour. In this paper, the influence of such behaviour on the hygrothermal response of a building wall is discussed. An experimental facility is designed to measure temperature and relative humidity within a hemp concrete wall submitted to climatic variations. This facility provides a set of experimental data suited for benchmarking. Numerical simulations are performed with a hysteresis model implemented in a heat and moisture transfer model. Comparisons between numerical and experimental results show that hysteresis modelling is relevant to simulate the hygrothermal response of the wall. The discussion is extended to the influence of the initial moisture content.